2015
DOI: 10.5194/amt-8-195-2015
|View full text |Cite
|
Sign up to set email alerts
|

Observations of volcanic SO<sub>2</sub> from MLS on Aura

Abstract: Abstract. Sulfur dioxide (SO 2 ) is an important atmospheric constituent, particularly in the aftermath of volcanic eruptions. These events can inject large amounts of SO 2 into the lower stratosphere, where it is oxidised to form sulfate aerosols; these in turn have a significant effect on the climate. The MLS instrument on the Aura satellite has observed the SO 2 mixing ratio in the upper troposphere and lower stratosphere from August 2004 to the present, during which time a number of volcanic eruptions have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…Durant and Rose, 2009). An alternative method based on the ratio of water vapour to SO 2 and the known mass of emitted SO 2 would give a low bias for the magmatic water mass for these two studied eruptions because the emitted mass of SO 2 from these eruptions was unusually low (Pumphrey et al, 2015;Vernier et al, 2013;Nakamae et al, 2014;Sears et al, 2013). Volcanic emissions are known to be more variable in terms of SO 2 than water vapour (Pinto et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Durant and Rose, 2009). An alternative method based on the ratio of water vapour to SO 2 and the known mass of emitted SO 2 would give a low bias for the magmatic water mass for these two studied eruptions because the emitted mass of SO 2 from these eruptions was unusually low (Pumphrey et al, 2015;Vernier et al, 2013;Nakamae et al, 2014;Sears et al, 2013). Volcanic emissions are known to be more variable in terms of SO 2 than water vapour (Pinto et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The SO 2 masses used in the present modelling study are indicated in bold. (2015) 562 Pumphrey et al (2015) 1350 (±38) 215 hPa Pumphrey et al (2015) 571 ( Concerning the measured and modelled SO 2 masses after the eruptions of Kasatochi and Sarychev (Fig. 6), comparisons show that until about 1 month after the eruptions, the SO 2 mass is by far underestimated by MIPAS.…”
Section: Sulfur Mass In the Northern Hemisphere Mid-and High Latitudesmentioning
confidence: 99%
“…Höpfner et al (2015) the given total uncertainty is the sum of the uncertainties per altitude range (their Table 3). In the case of Pumphrey et al (2015) pressure levels are given. These represent the highest pressure used for vertical integration.…”
Section: Sulfur Mass In the Northern Hemisphere Mid-and High Latitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ClO VMR frequently reaches 1.5 ppbv near 20 km during polar springtime due to the chlorine activation during the polar winter. The enhancement of SO 2 after strong volcanic eruption can also be measured (Pumphrey et al, 2015). EPP induced enhancement of NO x and HO x are an other example.…”
mentioning
confidence: 99%